Commercialisation activities in Malaysian Universities : issues and challenges / Ahmad Naqiyuddin Bakar ... [et al.] - Bakar, Ahmad Naqiyuddin; Omar, Abdul Rahman; Ambali, Abdul Rauf; Jaafar, Roseleena; Mohd Idris, Mohd Fadzil; Abd Majid, Zulkifli; Mohd Rom, Kamarol Baharen (Universiti Teknologi MARA, Shah Alam, 2016)
The study aims to examine issues of managing the innovation and commercialization activities in Malaysian Universities. Specifically, the aim of this study is to evaluate the perception of experienced researchers who have successful in their research product, in terms of patent and/or commercialization. Qualitative methods were applied to examine how individual researchers relate their personal experience against impending challenges in their endeavor. Despite remarkable macro level initiatives, the obvious lack of coherence policy instruments across institutional Ministries has dampened the progress. Consequently, the Intellectual Property and Commercialization (IP&C) Centre are operated within a less conducive eco-system within universities' parameter, thereby weakening their functional roles to make an impact externally. At the individual level of researchers, their traditional and structured worldview and philosophy about research undertaking could well be the hindrance. The study has highlights fundamental yet practical knowledge about commercialization issues, thereby supporting Malaysia's aspiration for an innovative economy.